Taeniasis and Cycticercosis/Neurocysticercosis (IntechOpen, 2024)
Taeniasis and Cysticercosis/Neurocysticercosis - Global Epidemiology, Pathogenesis, Diagnosis, and Management is a comprehensive and up-to-date overview of these two closely related parasitic diseases. The book covers all aspects of taeniasis and cysticercosis/neurocysticercosis, from epidemiology and pathogenesis to diagnosis and treatment. It also includes specific topics on the two Taenia species that infect humans, T. solium and T. saginata, and a third species, T. asiatica. This book is an essential resource for anyone wanting to learn more about taeniasis and cysticercosis/neurocysticercosis and how to prevent and control these diseases. It is written by leading experts in the field and includes the latest advances in epidemiology, diagnosis, treatment, and control. This volume is a useful resource for a wide audience, including researchers, clinicians, public health professionals, and students.